Pengaruh Modal dan Biaya Produksi Terhadap Pendapatan UMKM Bakso Solo Mas Kumis di Karawang - Della Sintya Rachman; Sihabudin, Sihabudin; Fauji, Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to test whether or not there is: the influence of Capital (X1) on Income (Y), the influence of Production Costs (X2) on Income (Y), and the influence of Capital (X1) and Production Costs (X2) on Income (Y). The type of research used in this study is quantitative research with an associative approach. The data in this study is to collect financial report data (Capital, Production Costs, and Income) of UMKM Bakso Mas Kumis Karawang in 2022-2023. With samples of Capital, Production Costs, and Income data from November 2022 to October 2023 (12 months). This study was conducted using purposive sampling. Researchers used four data collection methods, namely: documentation, observation, interviews, and literature reviews. Data analysis techniques used in this study are: descriptive test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test), hypothesis testing (multiple linear regression, partial test/t test, simultaneous test/f test), and coefficient of determination using SPSS 27. The results of the study indicate that: 1) The significance value of the Capital variable (X1) is 0.368, meaning that the significance value of 0.368> 0.05 indicates that the Capital variable does not have a significant effect on Income, meaning that the higher the Capital issued in the company's activities, the amount of Income will not necessarily increase. 2) The significance value of the Production Cost variable (X2) is 0.00, meaning that the significance value of 0.00 <0.05, indicates that the Production Cost variable has an effect on Income, meaning that the higher the Production Cost issued in the activity, the amount of Income achievement will increase. 3) The F-count value = 7.486 > F-table = 4.10 and the significance value is 0.000 < 0.05, indicating that the Capital and Production Cost variables simultaneously or together have an effect on Income, meaning that if Capital and Production Costs increase together, this will be followed by an increase in Income.